2017
DOI: 10.1007/s40865-017-0064-7
|View full text |Cite
|
Sign up to set email alerts
|

The Employment-Crime Association for Individuals Convicted of a Sexual Offense in their Youth

Abstract: Objective We study the bi-directional relationship between employment and crime for individuals convicted for a sexual offense in their youth (JSO) and investigate the moderating influences of age and employment duration. Method A bi-variate dynamic binary choice model is developed to allow for interactions between employment and crime. The model takes into account statistical aspects such as state dependence and unobserved heterogeneity. Results For a sample of N = 493 JSO, who are observed in early adulthood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 74 publications
(127 reference statements)
0
3
0
Order By: Relevance
“…In the Dutch case, screening as an instrument of crime prevention has partly redistributed crime control tasks to employers, who have been persuaded in several ways, as discussed above, to increase their reliance on CoCs. A survey among 875 Dutch employers demonstrated that 78% say they require CoCs because they feel 'obliged' to so do, whereas interviews revealed that most of them do not know whether this is required by law or merely a requirement deriving from the internal policy of the company or organisation (Valk et al, 2006).…”
Section: The Responsibilisation Of Employersmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Dutch case, screening as an instrument of crime prevention has partly redistributed crime control tasks to employers, who have been persuaded in several ways, as discussed above, to increase their reliance on CoCs. A survey among 875 Dutch employers demonstrated that 78% say they require CoCs because they feel 'obliged' to so do, whereas interviews revealed that most of them do not know whether this is required by law or merely a requirement deriving from the internal policy of the company or organisation (Valk et al, 2006).…”
Section: The Responsibilisation Of Employersmentioning
confidence: 99%
“…The government thus seems to have succeeded in creating a culture of collective responsibilisation providing strong incentives for employers to resort to criminal record screening, even when this is not mandated by law as in most cases. Interestingly, a policy evaluation among various employers revealed that on average 40% perceived the CoC merely as an administrative burden without attaching any substantive value to it (Valk et al, 2006). What is more, a similar percentage would consider not requesting CoCs, or requesting them only in specific situations if they did not feel obliged to do so.…”
Section: The Responsibilisation Of Employersmentioning
confidence: 99%
See 1 more Smart Citation